Proceedings of the 2008 InSITE Conference 2008
DOI: 10.28945/3204
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Various E-Learning Components

Abstract: Learning that is facilitated by electronic technologies, otherwise known as e-Learning, can be either fully online, mixed mode (also known as hybrid), or web assisted; however, regardless of the delivery method, there are numerous tools and features at the disposal of students and instructors, and it is important for the e-learning community to examine both preferences and usage of these features. This paper presents the findings of a comprehensive study that examined the elearning perceptions and preferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
0
19
0
2
Order By: Relevance
“…Wells, de Lange and Fieger (2008) found that the use of technology in educational settings assists in the achievement of learning outcomes. Buzzetto-More (2008) and Sanders & Morrison-Shetlar (2002) report that student attitudes toward technology are influential in determining the educational benefits of online learning resources and experiences. Research conducted by Perera and Richardson (2010) suggests that the quality of the actual time spent online may be influential on learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wells, de Lange and Fieger (2008) found that the use of technology in educational settings assists in the achievement of learning outcomes. Buzzetto-More (2008) and Sanders & Morrison-Shetlar (2002) report that student attitudes toward technology are influential in determining the educational benefits of online learning resources and experiences. Research conducted by Perera and Richardson (2010) suggests that the quality of the actual time spent online may be influential on learning outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wells, de Lange, and Fieger (2008) found that the use of technology in educational settings assists in the achievement of learning outcomes. Buzzetto-More (2008) and Sanders and Morrison-Shetlar (2002) reported that student attitudes toward technology are influential in determining the educational benefits of online learning resources and experiences. Results from an investigation of WebCT Course Management Statistical Tools in this first-year introductory accounting unit revealed a positive relationship between the level of student engagement with online resources and their overall academic result.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The instruments were developed by the researchers and aligned with the primary aim of the research. The issues of reliability and validity were considered when designing the research instruments in the sense that research findings by previous researchers were taken into consideration when developing the instruments (Bellefeuille, 2006;Bersin & Associates, 2003;Buzzetto-More, 2008). …”
Section: Research Instrumentationmentioning
confidence: 99%